A Big Change Starts Small – Pronominal Clitics in 12-15th Century Old Russian Chronicles - Györfi, Beáta (Slavica, 2020)
East Slavic languages, in contrast with South and West Slavonic ones did not retain enclitic pronominals. In Old Russian (ОR) however, these forms were widely used. As manuscripts suggest, they dissapeared from the language by the end of the OR period, i. e. by the 15th-16th centuries. The paper gives an overview of the use of enclitic pronominals in the text of five OR chronicles relying on the diachronic corpus of Russian National Corpus. The analysis focuses on the distribution of clitic pronominals, their placement, clusterizing properties and deviating constructions. The last section is devoted to the placement of the investigated phenomenon in the complex of parametric variation envoked by the disintegration of the tense-aspect system.